2004
DOI: 10.1097/01.bsd.0000117544.88865.f0
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Massive Dural Ectasia Associated with Neurofibromatosis Type 1 Threatening Spinal Column Support

Abstract: We report the case of a girl with a dystrophic neurofibromatosis lumbar scoliosis with asymptomatic progression and spread of dystrophic characteristics over 18 years. Resorption of almost the entire anterior column of L1-L4 had occurred despite a previous posterior instrumentation and fusion. A vascularized fibula bone graft wrapped in titanium mesh was used as an anterior structural graft. With close follow-up, the need for this type of salvage surgery might have been averted. Further follow-up showed no gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 10 publications
0
13
0
1
Order By: Relevance
“…Successful posterior fusion with little progression of dural ectasia and spinal deformities, as observed in our case, has been reported [9]. The progression of dural ectasia and bone erosion despite surgical treatment has also been documented [6]. The best treatment method for dural ectasia has not been established.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Successful posterior fusion with little progression of dural ectasia and spinal deformities, as observed in our case, has been reported [9]. The progression of dural ectasia and bone erosion despite surgical treatment has also been documented [6]. The best treatment method for dural ectasia has not been established.…”
Section: Discussionmentioning
confidence: 54%
“…However, Kleuver et al [6] reported a case of dystrophic neurofibromatosis scoliosis with asymptomatic progression and spread of dystrophic changes in the lumbar spine that occurred over 18 years, despite previous posterior instrumentation and fusion. Therefore, we plan to continue further follow-up examinations of our patient to prevent a poor outcome in his adult life.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Ayrıca progresif vertebral erozyona neden olarak vertebralarda fraktür ve dislokasyonlara neden olabilirler. Ancak spinal kanal genişlediğinden nörolojik defisit gelişmesi nadirdir (16).…”
Section: Olguunclassified
“…Neurologic deficit rarely occurs because the spinal canal is widened. 4 These deformities have been known to progress and evolve during the course of disease, a phenomenon known as "modulation. "…”
mentioning
confidence: 99%